Hydrogen-Bonded Structure of Water in the Loop of Anchored Polyrotaxane Chain Controlled by Anchoring Density - Akada, Keishi; Yamazoe, Kosuke; Miyawaki, Jun; Maeda, Rina; Ito, Kohzo; Harada, Yoshihisa (Frontiers in Chemistry, 2021)
Hydrogen-bonded network of water surrounding polymers is expected to be one of the most relevant factors affecting biocompatibility, while the specific hydrogen-bonded structure of water responsible for biocompatibility is still under debate. Here we study the hydrogen-bonded structure of water in a loop-shaped poly(ethylene glycol) chain in a polyrotaxane using synchrotron soft X-ray emission spectroscopy. By changing the density of anchoring molecules, hydrogen-bonded structure of water confined in the poly(ethylene glycol) loop was identified. The XES profile of the confined water indicates the absence of the low energy lone-pair peak, probably because the limited space of the polymer loop entropically inhibits the formation of tetrahedrally coordinated water. The volume of the confined water can be changed by the anchoring density, which implies the ability to control the biocompatibility of loop-shaped polymers.